High‐Temperature Photochromism of Fe‐Doped SrTiO3 Caused by UV‐Induced Bulk Stoichiometry Changes. (5th April 2019) - Viernstein, Alexander; Kubicek, Markus; Morgenbesser, Maximilian; Walch, Gregor; Brunauer, Georg Christoph; Fleig, Jürgen
Abstract: The impact of UV irradiation on Fe‐doped SrTiO3 (Fe:STO) single crystals is investigated at elevated temperatures. Illumination leads to incorporation of oxygen into the single crystals and thus to a decreasing oxygen vacancy concentration and oxidation of Fe 3+ to Fe 4+ . The Fe 4+ ions cause a color change from transparent/brownish to black. This photochromic blackening due to stoichiometry changes at elevated temperatures is irreversible at room temperature, but annealing at high temperatures, for example at 700 °C, can restore the original stoichiometry and color. Absorbance changes due to UV irradiation are monitored by ex situ and in situ UV–vis spectroscopy experiments and changes in electrical properties are measured by van der Pauw measurements and in‐plane electrochemical impedance spectroscopy. After 1140 min of illumination at 440 °C, for example, electrical measurements reveal a conductivity increase by more than a factor of 5 due to the enhanced hole concentration in blackened Fe:STO. In addition, UV illumination increases the oxygen chemical potential up to a calculated p (O2 ) of more than 10 9 Pa in Fe:STO. Hence, UV light can be used to tune the color, but also electrical properties of Fe:STO by directly impacting the bulk defect concentrations. Abstract : UV irradiation leads to oxygen incorporation into Fe‐doped SrTiO3 at elevated temperatures and thus the oxidation of Fe 3+ to Fe 4+, observable by a blackening of single crystals and enhanced conductivity. This photochromic process can be reversed by annealing the specimens at 700 °C.